Penyuluhan Napza Ke Sekolah di SMAN 1 Kutacane Tahun 2024 - Khalikul Fadli (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The abuse of Narcotics, Psychotropics, and Addictive Substances among the younger generation is a serious issue that threatens the future of the nation. This abuse has significant negative impacts on the mental and physical development of the younger generation. Therefore, prevention efforts through education, routine counseling, and positive activities in the community are crucial. The rampant abuse of Narcotics, Psychotropics, and other Addictive Substances among students and college students has become a new problem in the education sector. According to a survey conducted by the National Narcotics Agency (BNN) and the Indonesian Institute of Sciences (LIPI) in 2019, 2.3 million students or college students in Indonesia have consumed narcotics. The lack of knowledge and information among students about the effects of drug abuse is a major factor in the spread of this issue. The approach to implementing community service is carried out in several stages, including initial surveys, problem identification, needs analysis, target audience determination, and program implementation. Based on the community service activities carried out, the benefits are greatly felt. This is evident from the enthusiasm of the participants in engaging in the community service activities. The author would like to express their deepest gratitude to the Principal of SMAN 1 Kutacane, Southeast Aceh Regency, who has provided time and space and fully supported this community service activity so that it could be carried out successfully.